MASYARAKAT EKONOMI ASEAN (MEA) 2015 DAN TANTANGAN NEGARA KESEJAHTERAAN - Fathoni Fathoni (Supremasi Hukum: Jurnal Penelitian Hukum, 2015)
ABSTRACT  Indonesia is a sovereign state. The word here is not only sovereign denotatively meaning that the state government does not have power under the jurisdiction of another country. State government meant for the welfare of the people. When it is associated with free competition among countries, it can be more about the role of the state in protecting its citizens in order to avoid what is, according to Hobbes as "homo homini lupus". This is the challenge of the welfare state, which the state must not fail to welfare. The existence of cases of state failure to provide protection for its citizens, especially in free trade has become a scourge for the people. People who are not able to compete in free trade, in the end just be a spectator and does not play a role in the AEC 2015. State efforts to protect the people by improving competitiveness, increasing export volume, prioritizing the use of domestic goods / services. In the area of regulation, needs to set rules on security measures and monitoring domestic products to circulate goods and services, as well as by applying Early Warning System against the possibility of import surges.  Keywords: sovereign, state welfare, competitiveness, AEC 2015 ABSTRAKIndonesia adalah negara yang berdaulat. Kata berdaulat disini tidak saja bermakna denotatif bahwa negara memiliki kekuasaan pemerintahan yang tidak tunduk pada kekuasaan negara lain. Penyelenggaraan negara dimaksudkan untuk mewujudkan kesejahteraan rakyat. Bila dikaitkan dengan persaingan dengan negara lain, maka dapat ditarik lagi tentang peran negara dalam melindungi warganya agar tidak terjadi apa yang menurut Hobbes sebagai “homo homini lupus”. Inilah tantangan negara kesejahteraan tersebut, dimana negara tidak boleh gagal. Adanya kasus-kasus tentang gagalnya negara dalam memberikan perlindungan bagi warganya, terutama dalam perdagangan bebas telah menjadi momok bagi rakyat. Rakyat yang tidak mampu bersaing dalam perdagangan bebas, pada akhirnya hanya menjadi penonton dan tidak memainkan peranan dalam MEA 2015.Upaya negara dalam melindungi rakyat antara lain dengan meningkatkan daya saing, meningkatkan volume ekspor, mengutamakan penggunaan barang/ jasa dalam negeri. Di bidang regulasi, perlu ditetapkan peraturan tentang tindakan pengamanan produk dalam negeri dan pengawasan terhadap barang beredar dan jasa, serta dengan menerapkan Early Warning System terhadap kemungkinan terjadinya lonjakan impor. Kata kunci: berdaulat, negara kesejahteraan, daya saing, MEA 2015